Pengembangan Strip Tes Berbasis Pararosanilina untuk Deteksi Formalin pada Sampel Tahu - Alni Riskyna; Bambang Kuswandi; Indah Purnama Sary (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Test strip based on pararosaniline has been developed for formaldehyde detection in tofu samples. The test strip as a formaldehyde sensors has been fabricated by immobilizing pararosaniline on whatman filter paper. The test strip was characterized for liniearity, detection limit, quantitation limit, selectivity, accuracy and precision. It has response time at 4 minutes and good liniearity was achieved in the concentration range of 2-80 ppm with correlation coefficient of (r) 0.999. The detection limit and quantitation limit were 0.048 ppm and 0.161 ppm, respectively. The RSD of reproducibility was found 8.04%, where recovery was 80-110%. The life time of the test strip was 14 days when it was stored at 40C. The test strip has been successfully applied to detect formaldehyde in tofu samples. The result also shown in agreement with spectrophotometry uv-vis method. Keywords: formalin, pararosaniline, tofu, immobilization, strip test